Edge detection algorithm based on quantum superposition principle and photons arrival probability - Ayoub Ezzaki; Lhoussaine Masmoudi; Mohamed El Ansari; Francisco-Angel Moreno; Rachid Zenouhi; Javier Gonzalez Jimenez (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The detection of object edges in images is a crucial step employed in a vast amount of computer vision applications, for which a series of different algorithms has been developed in the last decades. This paper proposes a new edge detection method based on quantum information, which is achieved in two main steps: (i) an image enhancement stage that employs the quantum superposition law and (ii) an edge detection stage based on the probability of photon arrival to the camera sensor. The proposed method has been tested on synthetic and real images devoted to agriculture applications, where Fram & Deutsh criterion has been adopted to evaluate its performance. The results show that the proposed method gives better results in terms of detection quality and computation time compared to classical edge detection algorithms such as Sobel, Kayyali, Canny and a more recent algorithm based on Shannon entropy.